Pengaruh Model Discovery Learning Berbantuan Magic Straws Materi Bangun Ruang Terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Riza, Disma; Susanta, Agus; Juarsa, Osa (UNIB Press, 2024)
The purposes of this study is to determine the effect of using Discovery learning model magic straws assisted on the students to creative thinking ability. This research is a quantitative research. The method used in this study was the experimental method and descriptive method. The design of this study was Quasi Experimental with the Matching Only Pretest Posttest Control Group Design type. The subjects in this study were divided into two groups, that class VC students as the experimental group and class VA students as the control group. There are two instruments used to collect the data of this study were the observation guide and essay test of creative thinking ability which is given through posttest after the learning takes place. The test was carried out twice, before and after providing treatment, namely a Discovery learning Magic straws assisted in the experimental group. The data analysis technique used in this study were analyzed using field data, descriptive, inferential statistics (t-test), and N-gain test. The data analysis results show that average score of the posttest of two classes, the experimental class is 76.67 and the control class is 67.67. The t-test show that sig. (2-tailed) score is 0,003 < 0,025. The N-gain test shows a score of 66% which is in the good category. It can be concluded that there is a significant influence at the 5% level on the use of the Discovery learning Magic straws assisted on the students to creative thinking ablility.